The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3810/pgm.2013.07.2679
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Benign and Malignant Urologic Conditions

Abstract: Obesity, defined as a body mass index ≥ 30 kg/m² in adults by the National Institutes of Health, is associated with an increased risk for a number of health conditions, including hypertension, unfavorable lipid level, and diabetes mellitus. During the past 2 decades of the twentieth century, the prevalence of obesity has increased in the United States. In 2009 to 2010, 36% of adults were obese, including 41 million women and > 37 million men. In addition, the prevalence of metabolic syndrome (MetS), which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 209 publications
0
16
0
1
Order By: Relevance
“…The association of obesity with a poor clinical outcome in T1G3 NMIBC could be explained on the basis of several factors. In particular, it is well known that obesity is characterized by insulin resistance and low-grade systemic inflammation, which may affect the oncological outcomes of NMIBC patients as a result of insulin, IGF-1, cytokines and growth factors' effects [13]. In this regard, obese subjects showed increased levels of insulin and IGF-1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…The association of obesity with a poor clinical outcome in T1G3 NMIBC could be explained on the basis of several factors. In particular, it is well known that obesity is characterized by insulin resistance and low-grade systemic inflammation, which may affect the oncological outcomes of NMIBC patients as a result of insulin, IGF-1, cytokines and growth factors' effects [13]. In this regard, obese subjects showed increased levels of insulin and IGF-1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nutri tion and hormones, including insulin-like growth factor level, may influence the risk of developing prostate cancer (Key, 2014). Obesity and a prevalence of metabolic syndrome have been proven to be associated with prostate cancer (Chu, Rotker, & Ellsworth, 2013). Recent research has also shown an increased risk of prostate cancer with Agent Orange exposure (Ansbaugh, Shannon, Mori, Farris, & Garzotto, 2013).…”
Section: Medical Historymentioning
confidence: 99%
“…[17,[22][23][24][25] Development of renal cancer due to these conditions has been associated with inflammation, insulin, and insulin-like growth factor-1, renal hypoxia, hyperfiltration, and lipid peroxidation. [11,26] However in a study performed by Haggstrom et al [27] all components of metabolic syndrome have been correlation with the development of renal cancer. Increased body mass index, hypertension, hyperglycemia and hypertriglyceridemia especially in men and increased body mass index especially in women have been found to be important adverse factors.…”
Section: Renal Cancermentioning
confidence: 99%
“…However, various studies performed have detected an association between metabolic syndrome and infertility, stone disease, overactive bladder, female urinary incontinence, benign prostatic hyperplasia, prostate cancer and renal cancer. [9][10][11] In the light of the data obtained, the association between metabolic syndrome, and development of malignity has attracted attention of many researchers. In a recent review article this issue has been analyzed in detail.…”
mentioning
confidence: 99%